Analysis of the Health Level of Bank (BPRS) Amanah Ummah Bogor Before and During the Covid-19 Pandemic (2019-2020 Period) - Sukarsih, Cicih; Nurhayati, Immas (inovator, 2024)
The 2019 Coronavirus Disease (COVID-19) pandemic that hit the territory of Indonesia had a significant impact on the real sector including micro, small and medium enterprises, which greatly affected the performance of banks, including Islamic people’s financing banks. The performance of the BPRS has slowed down a bit along with the Covid-19 pandemic. Referring to the regulation (OJK) Number 20/PJOK.03/2019, the purpose of this study is to determine the soundness of the Amanah Ummah Sharia People’s Financing bank, in terms of aspects of capital, asset quality, profitability and liquidity. This type of comparative descriptive research. The data source is obtained primarily, from the financial statements for the 2019-2020 period. The results of the 2019 assessment: CAR of 25.47%, NPF of 2.62%, ROE of 27.87%. ROA is 3.31%, and CR is 20.82%. The results of the 2020 assessment: CAR of 18.40%, NPF of 3.74%, ROE of 24.10%, ROA of 2.99 and CR 21, 11%. There was an insignificant decrease in 2020 in the capital ratio and profitability ratio but still ranked 1. Conclusion BPRS Amanah Ummah before the pandemic and during the covid-19 pandemic the criteria for assessing the bank’s soundness level was ranked 1, VERY HEALTHY statement.